Development of Insulating Compositions for Watered Oil Wells to Improve the Environmental State of Oil Producing Regions - Shavkat Farkhadovich Khodzhaev, Ubaydulla Abidzhanovich Safaev (Mathematical Statistician and Engineering Applications, 2022)
The issues of formation waters produced with oil, their impact on the ecosystem as a whole are raised. The ecological aspects of selective isolation in oil wells are widely considered. Data on modern insulating reagents, their effectiveness, as well as ongoing research in our Republic on the creation of water-insulating compositions are given.